The Emotional Experience behind Sexually Offending in Context: Affective States Before, During, and After Crime Events. (March 2018) - Leclerc, Benoit; Lindegaard, Marie Rosenkrantz
Objectives: The current study focused on the role of affective states in adult sexual offending. We look at the prevalence of a range of affective states throughout sexual crime events. We break down the crime event into three stages—immediately before, during, and after the offense. We examine transitions of affective states—stage by stage—but also across victims. Finally, we investigate the impact of situational factors on affective states. Method: The sample consisted of a total of 553 adult males who had been convicted of a sexual offense. Self-report data on sexual crime events were collected from these offenders. Apart from descriptive and bivariate analysis, "affective state-switching patterns" are investigated through transition matrices. Results: Findings show large variations in affective states before, during, and after the offense but show little variation across victims. Alcohol usage and offender–victim relationship were related to affective states of offenders. Conclusions: We conclude that the found association between affective states and decision-making of sexual offenders calls for more research on within crime event variations especially, and future research should focus on causal mechanisms related to affective states.